2016
DOI: 10.3109/09553002.2016.1144942
|View full text |Cite
|
Sign up to set email alerts
|

Life-span exposure to sinusoidal-50 Hz magnetic field and acute low-dose γ radiation induce carcinogenic effects in Sprague-Dawley rats

Abstract: Background In 2002 the International Agency for Research on Cancer classified extremely low frequency magnetic fields (ELFMF) as a possible carcinogen on the basis of epidemiological evidence. Experimental bioassays on rats and mice performed up to now on ELFMF alone or in association with known carcinogens have failed to provide conclusive confirmation. Objectives To study the carcinogenic effects of combined exposure to sinusoidal-50 Hz (S-50 Hz) magnetic fields and acute γ radiation in Sprague-Dawley rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
4
17
0
1
Order By: Relevance
“…For example, rats treated with aspartame at low doses from pre‐natal life have been reported to develop higher incidence of malignant tumours compared with rats first treated at maturity. In agreement with the low‐dose hypothesis of carcinogenesis, rats exposed to 50 Hz magnetic fields during pre‐natal have been shown to later exhibit enhanced carcinogenic‐induced responses to formaldehyde and gamma radiation . These experimental examples demonstrate how early‐life exposures may potentially impact disease risks in later life, sometimes after a substantial latency period.…”
Section: Vulnerable Developmentsupporting
confidence: 58%
“…For example, rats treated with aspartame at low doses from pre‐natal life have been reported to develop higher incidence of malignant tumours compared with rats first treated at maturity. In agreement with the low‐dose hypothesis of carcinogenesis, rats exposed to 50 Hz magnetic fields during pre‐natal have been shown to later exhibit enhanced carcinogenic‐induced responses to formaldehyde and gamma radiation . These experimental examples demonstrate how early‐life exposures may potentially impact disease risks in later life, sometimes after a substantial latency period.…”
Section: Vulnerable Developmentsupporting
confidence: 58%
“…The results of the present study suggest that direction of the ELF field is an important experimental parameter and might be critical for induction of biological effects. It may be of interest that horizontal 50 Hz MFs were used in the recent animal carcinogenicity study reporting positive findings [21]. The results of the present study also show that the difference in the biological effects of vertical and horizontal ELF magnetic fields is similar in two different in vitro experimental models, exposed using two different exposure systems to two different ELF frequencies.…”
Section: Discussionsupporting
confidence: 74%
“…Evidence indicated that both TGFβ and p53 pathways might be involved in mammary tumor susceptibility to non-targeted radiation [31]. Single or repeated low-dose irradiation could result in accumulation of persisting DNA damage foci in cortical neurons, adversely affecting brain tissue and increasing the risk of carcinogenesis [32, 33]. Although such findings from animal experiments are not directly applicable to humans, these data can substantially add to our knowledge on the relationship between a wide range of ionizing radiation dose and cancer risk [34].…”
Section: Ldir and Ldrir-induced Bionegative Effects In Animal Modelsmentioning
confidence: 99%